Le Paradoxe du modèle atomique de Bohr. Acte et obstacle épistémologique dans la conception de la matière - Velanes, David (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
Bohr’s atomic model caused a revolution in the history of atomistics. Besides establishing a rupture with the traditional conceptions about atoms, it contributed to the development of quantum mechanics and, therefore, to a better understanding about matter. However, knowledge advances incessantly, as Bachelard teaches. The Bohrnian atomic model has become infecund for the objective understanding of material phenomena. If, on the one hand, it has enabled a significant advance in scientific knowledge towards a better understanding of the world, on the other hand, it has become an element of knowledge disruption. It is this paradox that this article aims to demonstrate in the light of Bachelardian ideas. Bohr’s nuclear atom model can be thought of as an act and as an epistemological obstacle in understanding the contemporary notion of matter. Keywords: Bachelard, Bohr, Rupture, Obstacle, Matter.